Conceptual Security Framework to mitigate risks in organizational policies while transforming to Industry 4.0 - Saba Khalil Toor; Waqar Azeem; Mubashar Mushtaq; Aftab Ahmed Malik; Zain Ul Haq; Haroon Ur Rashid Kayani (International Journal for Electronic Crime Investigation, 2024)
The manufacturing industry has undergone a radical transformation with the emergence of Industry 4.0, characterized by the convergence of Cyber-Physical Systems, Artificial Intelligence, Machine Learning, the Internet of Things, and big data. This fourth industrial revolution enables real-time monitoring and prompt decision-making. However, organizational policies pose significant challenges to its adoption, particularly regarding cybersecurity risks. This study investigates these challenges and proposes strategies for mitigation. Conducted in Pakistan, this mixed-methods research employs both quantitative (survey) and qualitative (interviews) approaches. The findings highlight the need for increased awareness, secure communication channels, interoperability, robust policies, and expert talent. Key challenges include data theft risks in global collaboration and weak organizational procedures. A conceptual framework addresses these issues, ensuring a secure and resilient transformation to Industry 4.0.